Comparison of the Active Sitting Test and Head-Up Tilt Test for Diagnosis of Postural Tachycardia Syndrome in Children and Adolescents - Cai, Hong; Wang, Shuo; Zou, Runmei; Liu, Ping; Li, Fang; Wang, Yuwen; Wang, Cheng (Frontiers in Pediatrics, 2021)
Objectives: We aimed to compare the hemodynamic responses to the active sitting test with the passive head-up tilt test (HUTT) in children and adolescents with postural tachycardia syndrome (POTS). We hypothesized that sitting tachycardia was also present in the POTS patients during sitting. Materials and Methods: We tested 30 POTS patients and 31 control subjects (range 9-16 years, mean age 12 years), who underwent both active sitting test and HUTT successively. We measured heart rate (HR) and blood pressure (BP) during each test. Results: For both POTS patients and control subjects, HUTT produced significantly larger HR and BP increases from 3 min to 10 min of postural change than the sitting test did. Moreover, the POTS patients with excessive orthostatic tachycardia during HUTT also had significantly larger increase in HR at all test intervals during the sitting test than control subjects. And a maximum increase in HR ≥ 22 bpm within 10 min of sitting test was likely suggested to predict orthostatic tachycardia, yielding a sensitivity and specificity of 83.3% and 83.9%, respectively. Only 6 of 30 POTS patients (20%) reached the 40-bpm criterion during the sitting test, and no one complained about sitting intolerance symptoms. Conclusions: We have shown that POTS patients also have sitting tachycardia when changing from a supine position to a sitting position. We believe that the active sitting test is a reasonable alternative maneuver in assessing POTS in population groups that cannot tolerate standing test or HUTT.